PENGEMBANGAN PEDOMAN UMUM PENERAPAN METODE ENHANCED OIL RECOVERY MENGGUNAKAN KORELASI DAN SENSITIVITAS PARAMETRIK - Ismail Rendhi Prakoso, Muhammad
Enhanced Oil Recovery (eor) is a method to increase the recovery from an oilfield. Generally EOR method are categorized to 3 category which are thermal, miscible gas and chemical. Examples of thermal are steam drive and in-situ combustion. Miscible gas are representated by CO2 flooding, while the examples of chemical are surfactant and polymer. Guideline for EOR Implementation is an important tools to be applicated in other field in the future. To construct it, 5 correlation equations are used which are generated from field in U.S.A. Data from field which used spesific EOR method are mandatory to get better results. To get a better view of the guidline, literature screen criteria properties of oil and reservoir used for these EOR methods are also reviewed. Besides calculating the recovery factor, the relationship between recovery with other parameters are also studied in parametric sensitivity. From the result of recovery efficiency from each method, for thermal EOR steam drive yield 34,81% which is higher than in-situ combustion which yield 28,12%. From the in-situ correlation, the recovery efficiency could surprass steam drive if the cummulative air injection (Ai) are modified. The surfactant method give 42,98% of recovery efficiency, which is the highest compared to 4,41% of polymer and 18,67% of CO2 flooding. The operational parameter of Volume CO2 injected in CO2 method can give significant increase in recovery efficiency. The values of maximum and minimum of recovery factor for each methods based on screening criteria of oil and reservoir propertis are summarized in this paper into a general guideline of Enhanced Oil Recovery implementation.